The Role of ClpB in Bacterial Stress Responses and Virulence - Alam, Athar; Bröms, Jeanette E.; Kumar, Rajender; Sjöstedt, Anders (Frontiers in Molecular Biosciences, 2021)
Bacterial survival within a mammalian host is contingent upon sensing environmental perturbations and initiating an appropriate counter-response. To achieve this, sophisticated molecular machineries are used, where bacterial chaperone systems play key roles. The chaperones are a prerequisite for bacterial survival during normal physiological conditions as well as under stressful situations, e.g., infection or inflammation. Specific stress factors include, but are not limited to, high temperature, osmolarity, pH, reactive oxidative species, or bactericidal molecules. ClpB, a member of class 1 AAA+ proteins, is a key chaperone that via its disaggregase activity plays a crucial role for bacterial survival under various forms of stress, in particular heat shock. Recently, it has been reported that ClpB also regulates secretion of bacterial effector molecules related to type VI secretion systems. In this review, the roles of ClpB in stress responses and the mechanisms by which it promotes survival of pathogenic bacteria are discussed.